2009
DOI: 10.1158/0008-5472.can-08-2394
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Systemic Buffers in Reducing Intratumoral Extracellular pH and Acid-Mediated Invasion

Abstract: A number of studies have shown that the extracellular pH (pHe) in cancers is typically lower than that in normal tissue and that an acidic pHe promotes invasive tumor growth in primary and metastatic cancers. Here, we investigate the hypothesis that increased systemic concentrations of pH buffers reduce intratumoral and peritumoral acidosis and, as a result, inhibit malignant growth. Computer simulations are used to quantify the ability of systemic pH buffers to increase the acidic pHe of tumors in vivo and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
158
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 40 publications
(47 reference statements)
4
158
1
Order By: Relevance
“…The latter has been successfully applied in mouse models to change the tumor metabolism, thereby reducing aggressiveness and metastasis. 11,12 Our results now suggest that counteracting tumor acidosis by neutralization could unleash an additional tumor-destructive mechanism by helping maintain CTL activity.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The latter has been successfully applied in mouse models to change the tumor metabolism, thereby reducing aggressiveness and metastasis. 11,12 Our results now suggest that counteracting tumor acidosis by neutralization could unleash an additional tumor-destructive mechanism by helping maintain CTL activity.…”
Section: Discussionmentioning
confidence: 73%
“…Targeting of select pathways provides an explanation for the observed split inhibition where CTL cytokine response was completely blocked while granule exocytosis was only partly inhibited in lactic acid milieu. The reversibility of CTL inhibition by buffering the extracellular pH of the lactic acid milieu suggests that neutralization of the tumor milieu might not only suppress metastatic capacity, as has been suggested, 11,12 but could also improve the targeting of the tumor by immune effector cells, thereby enhancing the effect of ATT.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…An inevitable consequence of aerobic glycolysis is the production of lactic acid [3,4]. Studies have shown that the extracellular pH of normal cells is in the range of 7.2 to 7.5, whereas the extracellular pH of cancer cells is in the range of 6.2 to 6.9 which is caused by aerobic glycolysis [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…19 Interestingly, recent reports have demonstrated that tumoral acidosis can be reduced by increasing systemic concentrations of pH buffers, inhibition of carbonic anhydrase IX and proton pump, which leads to suppression of malignant growth, suggesting the potential exploitation of the pH environments for the treatment of cancer. 12,[20][21][22][23] Moreover, changes in extracellular pH also play important roles in immune function, bone function and the nervous system.…”
Section: Introductionmentioning
confidence: 99%